International regulatory and publicly-funded initiatives to advance drug repurposing - Spin, Eva Louise; Mantel-Teeuwisse, Aukje K.; Pasmooij, Anna Maria Gerdina (Frontiers in Medicine, 2024)
Introduction Although drug repurposing holds great potential in addressing unmet needs, successful practical implementation is challenging and has been less widespread than anticipated. Regulators may play a critical role in addressing this, and recent years have seen the conception of regulator-initiated and publicly-funded repurposing initiatives, with significant regulator involvement. Methods International regulators and public funders (n = 8) were interviewed to obtain insight in how repurposing can be advanced from a regulatory perspective. Transcripts were thematically analyzed. Results Most initiatives employed a broad concept of repurposing. While patient access was the main focus, label extension remained the gold standard. Commonly perceived barriers were a lack of regulatory expertise, limited downstream drug development, insufficient financial incentives, inadequate awareness of challenges, and poor collaboration. Ways for regulators to facilitate repurposing include early and accessible involvement fostering education, collaboration, and awareness. Increased stakeholder engagement, including internationally, was recommended. Legislative changes may enable the current repurposing ecosystem to evolve. Discussion Regulators may play a central role in advancing repurposing by reconsidering their responsibilities within the current regulatory framework, both in mitigating repurposing pitfalls and actively encouraging repurposing initiatives by industry and non-traditional drug developers.